Understanding of national identity for the national judiciary of Germany in the context of Art. 4(2) TEU. Potential limitations on European integration - Lake, Leoni (Riga Graduate School of Law, 2023)
This Master's thesis deals with the different understanding of the German Constitutional Court of Art. 4(2) TEU in comparison to the understanding of the ECJ and its possible effects on the integration process. It addresses the reservations of control of EU measures, namely identity control and ultra vires control, developed by the German Constitutional Court in a comprehensive case law and the resulting non-application of EU law in the event of a violation of Germany's national identity. However, these reservations contrast the case law of the ECJ, which prohibits taking Art. 4(2) TEU and national identity as a basis for reviewing EU law and declaring it inapplicable. Nevertheless, these reservations are exercised in a pro-European manner and to a limited extent, so that there are no significant limitations to the integration process and no threat to the uniformity of EU law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Treaty on European Union; European integration process; National identity; Germany